Basic Research and Knowledge Production Modes: A View from the Harvard Medical School. (March 2016) - Boggio, Andrea; Ballabeni, Andrea; Hemenway, David
A robust body of literature analyzes the shift of academic science toward more business-oriented models. This paper presents the findings of an empirical study investigating basic scientists' attitudes toward publicly funded basic research at the Harvard Medical School and affiliated institutions. The study finds that scientists at the Harvard Medical School construe publicly funded basic research as inquiries that, whether use oriented or not, must be governed by the cognitive and social norms of the traditional mode of knowledge production (mode 1 paradigm). They recognize that academic science is vulnerable to access by external capital but maintain that it remains distinct from research done in the private sector. Overall, the study demonstrates that important segments of academia have preserved a traditional approach to knowledge production, which is yet to be transformed by the entrepreneurial turn.